Study of Potential Food Waste in Zero Waste Cities Area- Saridewi, Denpasar-Bali - I Nengah Muliarta; Catur Yudha Hariani; Ni Made Indra Wahyuni; A.A Tatik Rismayanti (Postgraduate, University of Mataram, 2023)
Food waste affects food security, the environment, and the economy in practically every country. The amount of food that is thrown away should be enough to feed the world's hungry people. Denpasar, as a large city with a growing population and a growing number of tourists, has food waste management issues. Unfortunately, no research has been done in the Denpasar City region on the possibility of food waste. This study aims to look at the possibilities of food waste in Denpasar's Saridewi area. The goal is to calculate the quantity of food wasted in communities that have implemented the zero-waste city concept for a year. The survey and observation methods were applied in this research. The survey was carried out by distributing a questionnaire, and observations were taken by weighing the food waste generated by households in the Saridewi suburb. The findings reveal that Saridewi inhabitants have adopted the zero-waste concept in food waste management, converting food waste into compost, animal feed, and others. One of the factors contributing to the generation of food waste in Saridewi is the practice of buying food ingredients and raring food without planning. On average, Saridewi residents produce food waste of 0.14 kg/person/day.